Reflections after Thirty Years - Payton, James R. (Occasional papers on religion in Eastern Europe, 2020)
"All this awareness shaped my hopes for what might transpire in the wake of the remarkable changes enacted in the wake of 1989. Those hopes reverberated with what was expressed in a different field for the future of Eastern Europe in the aftermath of Communism’s collapse. I recall reading scholars much more gifted in things economic than I, hoping that the liberated nations of Eastern Europe might develop a "third way," between capitalism and Communism. Much as that was talked about, however, the story of the past three decades reveals that no such economic third way has been discovered. I had hoped-as did many others-that the nations of Eastern Europe, with their rich heritage of deep religious commitments which had shaped their cultures in the times of their national zeniths, and had sustained their hopes in the nadirs of imperial and then Communist repression, might develop a "third way" in this area, too."